Pembuatan Ukiran Logam Sebagai Dekorasi Produk Keramik di Narka'S Silver Celuk, Sukawati, Gianyar - Sukajaya, I Komang; Mudra, I Wayan; Ngidep Wiyasa, I Nyoman (Hastagina : Jurnal Kriya Seni, 2025)
Decor ceramic generally use rattan , woven ate and metal materials , in particular hiyasan made from metal Still are plain and some have apply carving metal on the lamp ornamental made from ceramics . As stated in Asmara research . et al ., (2020). Decor ceramics are still minimal, namely is something interesting phenomenon For explored in make it happen decor ceramic using carving techniques metal . Art carve metal is art carve Indonesian traditional which involves the process of sculpting and carving metal For create various shapes and motifs. Art This own characteristic unique and diverse specialties , as well used For beautify various objects and accessories . Art carve metal is also a part important from wealth and inheritance art appearance Indonesian traditional (omahbse.co, 2023). Related with That How ornamental shapes and motifs applied to metal For mebut decor ceramics , processes and forms product after applied with carving metal. . The method used in the creation of this work is exploration (searching for sources of ideas, concepts and foundations of creation), design (design of the work) and embodiment (creation of the work). The creation process includes the stages of making sketches, stages of metal carving, installation of gems and installation of inlays on ceramic media, to produce beautiful and functional works. Related with explanation above the ISI Denpasar Institute is one of the arts education institutions in Bali , with give opportunity for student in step up and join in role in existing crafts in Bali for example in art carve metal